Maternal atopy and offspring epigenome-wide methylation signature - Hanna Danielewicz; Artur Gurgul; Anna Dębińska; Grzegorz Myszczyszyn; Tomasz Szmatoła; Anna Myszkal; Igor Jasielczuk; Anna Drabik-Chamerska; Lidia Hirnle; Andrzej Boznański (Epigenetics, 2021)
The increase in the prevalence of allergic diseases is believed to partially depend on environmental changes. DNA methylation is a major epigenetic mechanism, which is known to respond to environmental factors. A number of studies have revealed that patterns of DNA methylation may potentially predict allergic diseases. Here, we examined how maternal atopy is associated with methylation patterns in the cord blood of neonates. We conducted an epigenome-wide association study in a cohort of 96 mother-child pairs. Pregnant women aged not more than 35 years old, not currently smoking or exposed to environmental tobacco smoke, who did not report obesity before conception were considered eligible. They were further tested for atopy. Converted DNA from cord blood was analysed using Infinium MethylationEPIC; for statistical analysis, RnBeads software was applied. Gestational age and sex were included as covariates in the final analysis. 83 DM sites were associated with maternal atopy. Within the top DM sites, there were CpG sites which mapped to genes SCD, ITM2C, NT5C3A and NPEPL1. Regional analysis revealed 25 tiling regions, 4 genes, 3 CpG islands and 5 gene promoters, (including PIGCP1, ADAM3A, ZSCAN12P1) associated with maternal atopy. Gene content analysis revealed pointwise enrichments in pathways related to purine-containing compound metabolism, the G1/S transition of the mitotic cell cycle, stem cell division and cellular glucose homoeostasis. These findings suggest that maternal atopy provides a unique intrauterine environment that may constitute the first environment in which exposure is associated with methylation patterns in newborn.